Können als Apriori des Verstehens (mathematica didactica, 2019)
Easy access to tablets and smartphones in class suggests outsourcing ‘mechanical' handling of terms, equations, etc. to these devices to gain time for understanding. The article, however, wants to show that understanding on the higher level presupposes a 'mechanical' ability on the lower level. Relevant findings of philosophical phenomenology show that concepts by which we think are rooted in the usual way of dealing with things. The 'mechanical’ skill is not only mindless mechanics, but is the habit, which we must immediately access in understanding the higher level. The meaning of the practice is not speed, but essentially immediacy.